The Role of Education and Knowledge Science of Digital Era in The Perspective of Critical Thinking Teaching Method Norman Fairclough - Putri Retnosari; Rizal Mustansyir; Hastanti Widy Nugroho (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
The research entitled